(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In modern conditions the formation of the humanitarian paradigm is characterized by the fact that it changes significantly the philosophy and methodology of the analysis of science and art, which involves their cultural philosophic understanding in the aspect of the humanistic, value relationship. In accordance with the new culturogical installation the article explores the role of art in scientific creativity factors. The author on the basis of system-comparative analysis shows that the scientific picture of the world consists mainly of the natural properties of reality, whereas in art – its aesthetic and moral characteristics. These features enriching a work of art, creating its multiple meanings, inexhaustible and complicating its semantic structure, depend on the nature of a coherent artistic creative process, the fullness of its perception of the world. The idea is defended that aesthetic factors of artistic picture of the world, affecting the scientific creativity are important elements of knowledge. Keywords: science, art, the creative process, artistic perception, aesthetic sense, scientific creativity, artistic thinking